2022
DOI: 10.3390/bios12020075
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Virus Nucleic Acid via Isothermal Amplification on Plasmonic Enhanced Digitizing Biosensor

Abstract: Rapid detection for infectious diseases is highly demanded in diagnosis and infection prevention. In this work, we introduced a plasmonic enhanced digitizing biosensor for the rapid detection of nucleic acids. The sensor successfully achieved the detection of loop-mediated isothermal amplification for the hepatitis virus in this work. The sensor comprised a nanodisc array and Bst polymerases conjugated on the rough surface of a nanodisc. The rough surface of the nanodisc provided plasmonic hot spots to enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In this study, DNA could be measured by ten femtomolar levels without a target amplification step. Wei et al showed the digitalizing biosensor for the rapid detection of viral DNA using loop-mediated isothermal amplification (LAMP) and Au nanoarray [ 55 ]. The rough Au sensing surface could provide the hot spot to generate the MEF.…”
Section: Sensitive Plasmonic Nanobiosensors For Viral Dna Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, DNA could be measured by ten femtomolar levels without a target amplification step. Wei et al showed the digitalizing biosensor for the rapid detection of viral DNA using loop-mediated isothermal amplification (LAMP) and Au nanoarray [ 55 ]. The rough Au sensing surface could provide the hot spot to generate the MEF.…”
Section: Sensitive Plasmonic Nanobiosensors For Viral Dna Detectionmentioning
confidence: 99%
“… Viral DNA-target SERS and electrochemical biosensors using plasmonic nanomaterials: ( a ) Schematic diagram of the SERS-active viral DNAs detection platform using rough-faced Au nanostructure with GO and Raman dye-functionalized AuNPs. This figure is reproduced from [ 55 ] (© 2022 American Chemical Society); ( b ) Schematics of the SERS-based sensitive DNA detection using hierarchic interfacial Au nanocube assembly. This figure is reproduced from [ 58 ] (© 2022 American Chemical Society); ( c ) Plasmonic AuNPs-assisted colorimetric biosensor for detection of HCV DNA.…”
Section: Figurementioning
confidence: 99%
“…In this Special Issue, Wei et al [ 22 ] investigated the rapid detection of virus nucleic acid via isothermal amplification on a plasmonic-enhanced digitizing biosensor. The development of rapid and accurate pathogen screening technology is of great significance for the early diagnosis and prevention of infectious diseases.…”
mentioning
confidence: 99%